Pengaruh Komitmen Organisasi terhadap Perilaku Karyawan Room Service di Industri Perhotelan - I Wayan Pantiyasa; I Made Darsana (Society, 2022)
This study aims to determine the effect of organizational commitment on Organizational Citizenship Behavior among room division employees of XYZ Hotels. The research method used was quantitative by collecting data on 45 respondents employed in the room division of XYZ Hotels. This was coupled with the use of questionnaires and literature studies. The data were analyzed with descriptive statistics and simple linear regression. The findings of this study show that organizational commitment provides a strong and significant influence on Organizational Citizenship Behavior. Therefore, this study concludes that organizational commitment has an effect of 18.6% with a significance of 0.016 on Organizational Citizenship Behavior among room division employees of XYZ Hotels. The correlation coefficient between the two variables is 0.432, which is quite strong.